The Effect of Discount Price on Impulsive Buying Mediated by Utilitarian Browsing in TikTok Shop (Empirical Study of Gen Z and Millennials in Jakarta) - Rourentsia Meylovsky; Ratlan Pardede (PT Publikasiku Academic Solution, 2025)
TikTok Shop, as a social commerce platform, is increasingly popular among Generation Z and millennial in Indonesia, particularly for skincare products. This phenomenon requires further investigation to understand the factors driving impulsive buying, especially considering utilitarian browsing as a mediating process. This study aims to analyze the influence of discount price on impulsive buying among TikTok Shop users while examining the mediating role of utilitarian browsing. This research adopts a quantitative approach, with data collected through online questionnaires distributed to 120 respondents from Generation Z and millennial residing in DKI Jakarta, who have purchased skincare products through TikTok Shop. The data analysis technique employed is Structural Equation Modeling (SEM) using SmartPLS 3.0 software, including testing the measurement model (outer model) and the structural model (inner model). The results of this study are expected to provide deeper insights into impulsive buying behavior and serve as a reference for social commerce industry players to optimize marketing strategies involving discount price to enhance consumer satisfaction and engagement.